2017
DOI: 10.1186/s13071-017-2020-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of community sanitation usage with soil-transmitted helminth infections among school-aged children in Amhara Region, Ethiopia

Abstract: BackgroundGlobally, in 2010, approximately 1.5 billion people were infected with at least one species of soil-transmitted helminth (STH), Ascaris lumbricoides, Trichuris trichiura, hookworm (Ancylostoma duodenale and Necator americanus). Infection occurs through ingestion or contact (hookworm) with eggs or larvae in the environment from fecal contamination. To control these infections, the World Health Organization recommends periodic mass treatment of at-risk populations with deworming drugs. Prevention of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 32 publications
2
33
1
1
Order By: Relevance
“…To our knowledge, this will be the rst large-scale survey conducted at national level. There have been many small-scale studies in different parts of the country that reported prevalence for STH and SCH [9,11,12,14,15,26]. However, none of those studies were conducted at a national scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this will be the rst large-scale survey conducted at national level. There have been many small-scale studies in different parts of the country that reported prevalence for STH and SCH [9,11,12,14,15,26]. However, none of those studies were conducted at a national scale.…”
Section: Discussionmentioning
confidence: 99%
“…They are generally dated (early 1970s to 2015; [5,9,13]), nor do they cover the entire country. Moreover, they differ considerably in sample size, design and diagnostic method utilized hindering direct comparison [9,12,14,15], which further complicates effectively designing and implementing MDA programs. Since 2000, the Ethiopian government has implemented STH deworming of children in under ve as part of an integrated vitamin A supplementation programme.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between use of pit toilets and decreased incidence of disease and helminth infection compared to open defecation has been addressed in the literature. Pit toilet usage can protect public health in two ways: 1) it can protect the health of the members of the household that uses the pit toilet (individual effect) or 2) it can protect the health of the community members surrounding the household that uses the pit toilet (community effect) (Komarulzaman et al, 2017;Jung et al, 2017;Oswald et al, 2017). It is unknown whether the individual effect or the community effect has greater influence.…”
Section: Epidemiology and Health Risk Evidence Associated With Pit Tomentioning
confidence: 99%
“…Anslostoma duodenale and Necater americanus are the common hookworm species. Humans become infected through skin penetration by infective larvae in the soil [1][2][3]. It mainly affects adults than preschool and school aged children.…”
Section: Introductionmentioning
confidence: 99%